Inovasi Pembelajaran Nahwu dalam Kurikulum Bahasa Arab Modern - Cholidah, Zahrotul; Muid, Faruq Abdul (Global Action and Education for Society, 2024)
The research examines innovations in nahwu learning in modern Arabic curricula, with the aim of improving student understanding and engagement. The research method used is a descriptive qualitative approach, involving the study of literature, document analysis, and interviews with Arabic education experts. Research findings show that the use of digital technologies, such as interactive learning applications and e-learning platforms, as well as the development of contextual teaching materials, significantly improved students' understanding of Arabic grammar by up to 30%. Student involvement also increased sharply by 50% when the learning methods used were more interactive and relevant to their lives. In addition, teachers responded positively to these innovations, with a 25% increase in positive responses. The results of this study underline the importance of adaptation in teaching methods to keep up with technological developments and the needs of modern students. Successful implementation of innovation requires the support of educational institutions, adequate training for teachers, and the development of sustainable learning resources. The research concludes that innovation in nahwu learning is effective in improving the quality of Arabic language education and must be continuously developed and widely applied to optimal results.